Discipline (and reversibility) in the training space of school football: a case study - Merino, Abel (2021)
Sports initiation takes place at a crossroads of sports, pedagogical and psychological interests. The monitoring of school sports requires the construction of a training discipline that underlines the promoted values in which the school-age child is formed. This study is interested in understanding the coordinates in which discipline is established in football, because it is one of the most important school sports, and the implications it has for the young athlete. A participant observation research design is used, in which 10 under 8 football teams participate during two school courses. Five qualitative categories emerge on the results: respect for an authority, commitment to an activity, preparatory routines, fissure in peer learning and behavior modeling. In the categories there are divergences between the coercive leadership of some coaches and the learning that schoolchildren build in their horizontal interaction. Families are an indispensable figure for the consolidation of the preparatory routines of the activity. The study concludes with the invitation to a reflection that converges in the educational interests of sports activity, whose purpose is to enhance its formative value and establish internal coherence.